History of the United Netherlands, 1588-89 - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"History of the United Netherlands, 1588-89" by John Lothrop Motley is a historical account written in the late 19th century. The book details the events surrounding the complex political and military struggles of the United Netherlands during a pivotal period in European history. It primarily focuses on the conflict between the Dutch states and Spain, highlighting the significant military campaigns, key figures, and the internal strife that impacted the struggle for independence and governance within the Netherlands. In this detailed narrative, Motley recounts the siege of Bergen-op-Zoom, illustrating the military strategies employed by both the Spanish Duke of Parma and the Dutch forces led by Colonel Morgan and other commanders. The author portrays the intense emotions and motivations of these leaders, revealing a sense of desperation and betrayal as Dutch cities turn against each other amidst rising tensions. Key events include the failed siege attempts, the factional disputes among English and Dutch allies, and the treachery of local commanders that ultimately resulted in the loss of crucial territories. Through rich descriptions and historical insights, the book provides a comprehensive view of the fight for Dutch independence, the interplay of foreign alliances, and the transformative political landscape of late 16th-century Europe. (This is an automatically generated summary.)
Release date is 2004-01-01
This eBook was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648